Ginger Constituent 6-Shogaol Inhibits Inflammation- and Angiogenesis-Related Cell Functions in Primary Human Endothelial Cells - Bischoff-Kont, Iris; Primke, Tobias; Niebergall, Lea S.; Zech, Thomas; Fürst, Robert (Frontiers in Pharmacology, 2022)
Rhizomes from Zingiber officinale Roscoe are traditionally used for the treatment of a plethora of pathophysiological conditions such as diarrhea, nausea, or rheumatoid arthritis. While 6-gingerol is the pungent principle in fresh ginger, in dried rhizomes 6-gingerol is dehydrated to 6-shogaol. 6-Shogaol has been demonstrated to exhibit anticancer, antioxidative and anti-inflammatory actions more effectively than 6-gingerol due to the presence of an electrophilic Michael acceptor moiety. In vitro, 6-shogaol exhibits anti-inflammatory actions in a variety of cell types, among them leukocytes. Our study focused on the effects of 6-shogoal on activated endothelial cells. We found that 6-shogoal significantly reduced the adhesion of leukocytes onto lipopolysaccharide (LPS)-activated human umbilical vein endothelial cells (HUVECs) resulting in a significantly reduced transmigration of THP-1 cells through an endothelial cell monolayer. Analyzing the mediators of endothelial cell-leukocyte interactions, we found that 30 µM of 6-shogoal blocked the LPS-triggered mRNA and protein expression of cell adhesion molecules. In concert with this, out study demonstrates that the LPS-induced nuclear factor κB (NFκB) promotor activity was significantly reduced upon 6-shogaol treatment. Interestingly, the nuclear translocation of p65 was only slightly decreased and protein levels of the LPS receptor toll-like receptor 4 remained unimpaired. Analyzing the impact of 6-shogaol on angiogenesis-related cell functions in vitro, we found that 6-shogoal attenuated the proliferation as well as the directed and undirected migration of HUVECs. Of note, 6-shogaol also strongly reduced the chemotactic migration of endothelial cells in the direction of a serum gradient. Moreover, 30 µM of 6-shogaol blocked the formation of vascular endothelial growth factor (VEGF)-induced endothelial sprouts from HUVEC spheroids and from murine aortic rings. Importantly, this study shows for the first time that 6-shogaol exhibits a vascular disruptive impact on angiogenic sprouts from murine aortae. Our study demonstrates that the main bioactive ingredient in dried ginger, 6-shogaol, exhibits beneficial characteristics as inhibitor of inflammation- and angiogenesis-related processes in vascular endothelial cells.